Factors Affecting the Success of Exclusive Breastfeeding among Working Mothers - Melan Saputra; Agustin Agustin; Rizky Meilando (Genius Journal, 2026)
Introduction: The target of national exclusive breastfeeding coverage is 80%. For three consecutive years, the Payung Village Health Center has an exclusive breastfeeding coverage rate of 48.19% in 2022, 56.31% in 2023 and 62% in 2024. Exclusive breastfeeding provides many benefits for the mother    and baby if it isstimulated, but it also provides a negative impact if exclusive breastfeeding is not stimulated  in the baby. ObjectiveThe purpose of this study is to find out the factors that affect the success of Exclusive Breastfeeding in the Working Area of the Payung Village Health Center in 2025.  Method: This study uses a Cross Sectional design. The population is working mothers who have 114 babies aged 6-24 months with a sample of 60 people. The sampling technique uses probability sampling with a simple random sampling type. The data analysis uses the chi square test. Result: The results of the study on working mothers who gave exclusive breastfeeding showed (68.9%) with good knowledge, (82.4%) good husband support, (78.1%) good work support. The results of the statistical test found that there was a meaningful relationship between knowledge (ρ0.001), education (ρ0.014), (husband support (ρ0.001), workplace support (ρ0.002) and the success of exclusive breastfeeding. Conclusion: There was a meaningful relationship between the variables of knowledge, education, husband support and workplace support with the success of exclusive breastfeeding. It is hoped that Health Institutions will be used as input and intervention materials in increasing the coverage of exclusive breastfeeding.